User Acceptance Testing through Blackbox Evaluation for Corn Distribution Information System - Zulkarnaini; Ayu Firdhayanti; Taufik Taufik; Bobby Bachry (Komunitas Dosen Indonesia, 2023)
Corn Distribution Information System in Bandar Lampung has witnessed a significant surge in interest, highlighting the importance of ensuring system reliability and functionality. This research endeavors to investigate and enhance these aspects through the application of the black box testing approach, focusing on the user-centric perspective of User Acceptance Testing (UAT). Black box testing, a methodology emphasizing system functionality without delving into internal structures, is complemented by UAT to provide comprehensive evaluation. In executing 27 study cases to evaluate the system, 22 patients demonstrated proper functionality, while 5 issues were identified. Notably, 4 issues pertained to the unavailability of the export function to CSV, and 1 patient encountered difficulties with road letter generation facilities. The discussion elucidates that UAT through Black Box proves to be a valuable approach, effectively bridging the methodological gap of traditional black box and providing insightful input from end users. Furthermore, this methodology successfully identified 5 focal points that can serve as development suggestions for the company's system, previously undiscovered. In conclusion, the study underscores the efficiency of integrating UAT with black box in enhancing Corn Distribution Information System's dependability and functionality. Identified issues shed light on areas for improvement, emphasizing the need for ongoing research in system testing methodologies. Future studies are recommended to explore the integration of UAT with white box testing, iterative testing for bug identification, and comprehensive security testing within the system network. This approach ensures a holistic evaluation, addressing potential limitations and contributing to the continuous refinement of the information system.